HUBUNGAN PANJANG BERAT DAN NISBAH KELAMIN UDANG KARANG MUTIARA (Panulirus ornatus) DI SEKITAR PULAU SALEMO KABUPATEN PANGKEP - Hasrun Hasrun; Kasmawati Kasmawati (JURNAL AKUAKULTUR, TEKNOLOGI DAN MANAJEMEN PERIKANAN TANGKAP, ILMU KELAUTAN, 2022)
The purpose of this study is 1) The composition of the type of catch of crayfish caught in the water around the island of Salemo. 2) Long-weight crayfish pearl (P. ornatus) and Sex ratio. This research will be conducted on October 1, 2021 to February 28, 2022 in the Salemo Island Waters in the Kabupatan Pangkep area. The research method used to identify the type of crayfish was carried out visually by looking at the color patterns found in the body segments based on the book Moosa and Aswandy (1984), identification of crayfish types was carried out using the identification key from William. The results of this study showed that there were 3 types of crayfish or lobsters, namely pearl crayfish (P. ornatus) as many as 38.23 heads or 38.23%, pearl crayfish (P. versicolor) as many as 218 heads or 41.05%, and batik crayfish (P. longipes) as many as 110 heads or 20.72%. With the largest size is pearl crayfish (P. ornatus). The sex ratio of male and female crayfish pearl crayfish (P. ornatus) is 0.45 : 0.55 or a ratio of 1 : 1. The relationship between the length and weight of pearl crayfish is classified as a minor allometric growth pattern.